High temporal resolution modeling of the impact of rain, tides, and sea level rise on water table flooding in the Arch Creek basin, Miami-Dade County Florida USA - Sukop, Michael C.; Rogers, Martina; Guannel, Greg; Infanti, Johnna M.; Hagemann, Katherine (The Science of the total environment, 2018)
Modeling of groundwater levels in a portion of the low-lying coastal Arch Creek basin in northern Miami-Dade County in Southeast Florida USA, which is subject to repetitive flooding, reveals that rain-induced short-term water table rises can be viewed as a primary driver of flooding events under current conditions. Areas below 0.9m North American Vertical Datum (NAVD) elevation are particularly vulnerable and areas below 1.5m NAVD are vulnerable to exceptionally large rainfall events. Long-term water table rise is evident in the groundwater data, and the rate appears to be consistent with local rates of sea level rise. Linear extrapolation of long-term observed groundwater levels to 2060 suggest roughly a doubling of the number of days when groundwater levels exceed 0.9m NAVD and a threefold increase in the number of days when levels exceed 1.5m NAVD. Projected sea level rise of 0.61m by 2060 together with increased rainfall lead to a model prediction of frequent groundwater-related flooding in areas<0.9m NAVD. However, current simulations do not consider the range of rainfall events that have led to water table elevations>1.5m NAVD and widespread flooding of the area in the past. Tidal fluctuations in the water table are predicted to be more pronounced within 600m of a tidally influenced water control structure that is hydrodynamically connected to Biscayne Bay. The inland influence of tidal fluctuations appears to increase with increased sea level, but the principal driver of high groundwater levels under the 2060 scenario conditions remains groundwater recharge due to rainfall events. [Display omitted] •Examines past and future groundwater-induced flooding in low-lying coastal area.•Record shows water table rising with sea level, enables future flooding estimation.•Groundwater model integrates rainfall, tidal fluctuations, and sea level rise.•Model projects frequency and intensity of 2060 groundwater-induced flooding.•Sea-level-rise-bellwether area imparts science, social, and policy relevance.